Greece : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for Greece. Two important steps toward improving fiscal transparency since the last ROSC update were Greece's subscription to the Special Data Dissemination Standard in November 2002, and participation in the preparation of the data module of the ROSC. Other steps included improving fiscal audits and the evaluation of budget expenditure, and measures in the recent tax reform to simplify the tax system.